2007
DOI: 10.2116/analsci.23.475
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electrochemical Detection of Ketorolac Tromethamine at Polypyrrole Modified Glassy Carbon Electrode

Abstract: Ketorolac tromethamine, KT ((k)-5-benzoyl-2,3-dihydro-1H pyrrolizine-l-carboxylic acid), is a member of the pyrrolopyrrole group of non-steroidal anti-inflammatory drugs 1 with cyclooxygenase inhibitory activity. 2 KT is a non-opioid analgesic which exists in three crystalline forms that are soluble in water. KT, when administered systemically, has demonstrated analgesic, anti-inflammatory, and anti-pyretic activity.3 KT is used for acute and short-term relief of pain. It increases the plasma levels of salicyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The signal intensity of SWSV was found to be 10 times higher that that of DPSV. Similar observation was found with SWSV for the trace analysis of few other drugs [29][30][31][32]. …”
Section: Constant Potential Chronoamperometrysupporting
confidence: 84%
“…The signal intensity of SWSV was found to be 10 times higher that that of DPSV. Similar observation was found with SWSV for the trace analysis of few other drugs [29][30][31][32]. …”
Section: Constant Potential Chronoamperometrysupporting
confidence: 84%
“…Composites of carbon nanotubes with Schiff base metal complexes (Amiri et al 2011), Cu(OH) 2 (Arvand et al 2012) and cysteic acid (Wang et al 2006) have been also reported. Electrode modification with polypyrrole film (Santhosh et al 2007), montmorillonite (Beltagi 2009), Ni-curcumin (Heli et al 2009), iron complexes (Hasanzadeh et al 2012), β-cyclodextrin (Balaji et al 2008) and chitosan-doped carbon nanoparticles ) complete the scope of antiinflammatory screening.…”
Section: Strategie Example Of Applicationmentioning
confidence: 99%
“…A range of methods are available for determining GNT and KET, including high-performance liquid chromatography (HPLC), 7–10 liquid chromatography-mass spectrometry (LC-MS), 11–14 capillary electrophoresis (CE), 15–17 electrochemical techniques, 18–20 and fluorometric methods. 21–23…”
Section: Introductionmentioning
confidence: 99%